Estudo fitoquímico das folhas e frutos de Piper caldense C.DC. (Piperaceae) - Silva, Gracielle Angeline Tavares da (2013)
The Piper L. genus is the largest one among the Piperaceae. Containing at least 1000 species, they are located mainly on the neotropical region of Earth and it draws our attention due to its medical, economical, chemical and cultural properties, such as anti-inflamatory, antibacterial and fungicide actions. Piper genus species have been becoming research sources for specific classes of secondary metabolites which play an important role concerning biological activities, including alkaloids, amides, chalcones, chromenes, flavonoids, lignans, terpenes, cyclopentanediones, steroids, porphyrin derivatives and benzoic acid derivatives. Piper caldense C. DC., which is commonly known as Pimenta D arda , is used in Paraíba as sedative, snake venom antidote, anti-toothache agent, and as active in located pain treatments through the use of compresses. This research reports the phytochemical study of P. caldense C. DC. leaves and fruits. Through usual chromatographic methods and spectroscopic techniques such as IR and one and two-dimensional ¹H and ³CNMR techniques and comparison with literature data it was possible to isolate and identify an mixture of the β-sitosterol and sitgmasterol steroids, besides porphyrin substances: 15-hydroxy-A-pophyrinlactone and a phaeophytin. Those fractions were obtained from crude ethanolic extract of P. caldense C. DC. leaves. Three benzoic acid derivatives were isolated from the hexane extract of P. caldense C. DC. fruits. From its leaves and fruits it was possible to obtain seven compunds commonly found it many vegetal species, but for the first time stated from P. caldense C. DC. The hexane and dichloromethane fruit extracts and isolated substances were submitted to microbiological assay and antifungal activites were detected concerning Candida genus yeast. This test is being done for the first time in the fruits of the studied species.